1997
DOI: 10.1046/j.1365-3083.1997.d01-425.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LPS and Plasmodium falciparum Induced Cytokine Secretion by Pentoxifylline and Two Analogues

Abstract: Jakobsen PH, Koch C, Bendtzen K. Inhibition of LPS and Plasmodium falciparum Induced Cytokine Secretion by Pentoxifylline and Two Analogues. Scand J Immunol 1997;45:546-550 Pentoxifylline and the two analogues HWA138 and HWA448, at concentrations exceeding 60 mg/ml, inhibited malaria antigen or lipopolysaccharide (LPS) induced TNF-a and IL-1a secretion, but not IL-6 secretion, from human peripheral blood mononuclear cells in vitro. HWA448 had lower inhibitory activity in vitro than pentoxyfylline and HWA138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In conclusion, our data show that HWA 448 limited muscle wasting by suppressing the activation of Ub-proteasome-dependent proteolysis, which plays a prominent role in the breakdown of muscle proteins, and was much more potent than pentoxifylline. In addition, HWA 448 did not alter peripheral blood mononuclear cell viability, and has a longer serum half-life and presumably lower toxicity than pentoxifylline, which is commonly used in humans [52]. Taken together, the data suggest that the administration of HWA 448 may contribute to the prevention of the muscle wasting seen in cancer and other catabolic states characterized by a hyperproduction of TNF, such as sepsis or trauma.…”
Section: Discussionmentioning
confidence: 84%
“…In conclusion, our data show that HWA 448 limited muscle wasting by suppressing the activation of Ub-proteasome-dependent proteolysis, which plays a prominent role in the breakdown of muscle proteins, and was much more potent than pentoxifylline. In addition, HWA 448 did not alter peripheral blood mononuclear cell viability, and has a longer serum half-life and presumably lower toxicity than pentoxifylline, which is commonly used in humans [52]. Taken together, the data suggest that the administration of HWA 448 may contribute to the prevention of the muscle wasting seen in cancer and other catabolic states characterized by a hyperproduction of TNF, such as sepsis or trauma.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, HWA 448 did not alter peripheral blood mononuclear cell viability, and has a longer serum half-life and presumably lower toxicity than pentoxifylline, which is commonly used in humans [52]. Taken together, the data suggest that the administration of HWA 448 may contribute to the prevention of the muscle wasting seen in cancer and other catabolic states characterized by a hyperproduction of TNF, such as sepsis or trauma.…”
Section: Discussionmentioning
confidence: 84%
“…Other laboratories have shown that the specific activation of macrophages decreases septic sequelae and improves survival in humans and experimental animals (3,7,11). Besides human macrophages, other immune-related cells respond to different molecules increasing resistance to infection (23,24,51). In this setting, for example, the involvement of T cells in the enhanced resistance to Klebsiella pneumoniae septicemia in mice treated with liposome-encapsulated muramyl tripeptide has been demonstrated (19).…”
Section: Discussionmentioning
confidence: 99%